English additional language undergraduate students’ engagement with the academic content in their curriculum in a South African speech-language and hearing training program - Khoza-Shangase, Katijah; Kalenga, Margo (Frontiers in Education, 2024)
Background: The emergence of the Speech-Language and Hearing (SLH) professions in South Africa took place during the era of racial segregation. Consequently, the culture and language of these professions have predominantly reflected the minority White population, even in SLH training programs. English has remained the language of learning and teaching (LOLT) in most South African tertiary institutions, with a strong Western cultural influence. Given the increasing diversity in these institutions, a mismatch between the language of instruction and that of English Additional Language (EAL) students poses academic challenges for this population, prompting the need for this study.Aim: This study aims to investigate the learning and social experiences of EAL undergraduate students enrolled in South African SLH training programs, with a specific focus on exploring their engagement with academic content in the curriculum. Methods: A cross-sectional online survey design was employed, and a total of twenty-four EAL students participated in the study. Descriptive and thematic analysis methods were utilized for data analysis.Results: The findings revealed that EAL students encountered academic challenges primarily related to their proficiency in the LOLT, which were most pronounced in lectures and examinations, while being relatively less pronounced in assignments. Complementary use of indigenous languages, simplification of complex terminology and self-employed strategies to cope in response to the existing academic language challenges are highlighted. These findings underscore the significance of addressing pedagogical approaches, language policies, and curriculum transformation towards a more Afrocentric perspective.The study highlights the academic difficulties faced by EAL students in South African SLH training programs. The implications for future interventions in this context are highlighted. The findings emphasize the need for pedagogical reforms, language policy considerations, and curriculum transformation that embraces Afrocentric perspectives. Addressing these issues is crucial to ensure equitable educational experiences and support the success of EAL students in the SLH field.